Chronic Eosinophilic Leukemia Presenting as Cardiac Failure - Boi-Doku Pepra-Ameyaw, Nii; Ghunney, William Kwasi; Baafi Ampofo, Eugene; Olayemi, Edeghonghon (Case Reports in Hematology, 2022)
Chronic eosinophilic leukemia (CEL) is a rare chronic myeloproliferative disorder characterized by sustained eosinophilia. Although the incidence of CEL is uncertain, it can be clinically devastating as it has a propensity to affect several important organ systems. This is of particular significance in Sub-Saharan Africa where helminthic infections are a more prevalent cause of eosinophilia. To the best of our knowledge, we present the first reported case of CEL complicated by cardiac disease in a Ghanaian. He presented with a history of orthopnoea and dyspnoea on exertion, and examination revealed a pansystolic murmur over the mitral region and moderate splenomegaly. Good symptomatic control was achieved using hydroxyurea after which haematologic and cytogenetic remission was achieved after 12 weeks on a tyrosine kinase inhibitor. Physicians working in low resource environments should exclude clonality in patients presenting with eosinophilia and end-organ damage.